STRUCTURAL-SEMANTIC FEATURES OF ABBREVIATIONS IN DIFFERENT LANGUAGES (Web of Teachers: Inderscience Research, 2024)
This article highlights the intricate ways in which abbreviations function across different languages, emphasizing the importance of structural and semantic considerations in their formation and use. Further research could explore the evolution of abbreviations in digital communication and their impact on language change.